Alternative Project Delivery Methods for Infrastructure: In the Context of Nepal - Yogesh Dhami, (International Journal of Scientific Research in Science and Technology, 2025)
Among several indicators used to assess the effectiveness of project execution are cost, schedule, and quality. In Nepal, issues such as cost overruns, delays, and substandard quality are ubiquitous in the public infrastructure sector, while public funds are consistently lagging far behind in delivering the basic infrastructure amenities. The main aim of this research is to review the most progressive models for public infrastructure delivery used in the global infrastructure sector and examine their applicability for Nepal. To fulfill the objectives, desk study methodology was employed, which includes an extensive analysis of pertinent literature, public reports, and articles concentrated on project delivery methods and their effectiveness and selection criteria. The study results substantiate the limitations of adopting the traditional Design-Bid-Build model for public infrastructure service delivery and conclude that alternative project delivery methods (PDMs) are likely to be more effective in addressing the predominant issues in Nepal. While this study put forward alternative PDMs as a solution for uplifting the infrastructure sector in Nepal, future research could greatly benefit from investigating other topics to provide more comprehensive solutions. Hence, the paper can be helpful for understanding the present scenario, practices, setbacks, and potential solutions for infrastructure development in the context of Nepal.
Keywords: Public Policies in Infrastructure Development; Alternative Project Delivery Methods; Public Private Partnership; Effective Infrastructure Development and Economic Growth; Public Infrastructure Projects